A new species of small Eptesicus Rafinesque (Chiroptera: Vespertilionidae) from northern South America - Ramírez-Chaves, Héctor E.; Morales-Martínez, Darwin M.; Pérez, Weimar A.; Velásquez-Guarín, Daniela; Mejía-Fontecha, Ingrith Y.; Ortiz-Giraldo, Mateo; Ossa-López, Paula A.; Páez, Fredy A. Rivera (Zootaxa, 2021)
Eptesicus diminutus Osgood, 1915 is the smallest species of the subgenus Eptesicus found in South America. It has a discontinuous distribution, with northern populations in Colombia and Venezuela, and southern populations in Argentina, Brazil, Paraguay, and Uruguay. We reviewed specimens assigned to the northern populations of E. diminutus and compared them to these from the southern populations. Based on morphologic, morphometric, and molecular analyses, we support the recognition of the northern populations of E. diminutus as a new species. This new species is distributed in the Llanos of the Orinoco region in Colombia and Venezuela (and likely in Guyana). Eptesicus sp. nov. is morphologically similar to E. diminutus and E. furinalis, from which it can be distinguished by its intermediate size. This taxon increases to 11 the number of species of bats of the subgenus Eptesicus in South America.